A survey on the language learning strategies used by the UHB 1412 students - 274390 Salveen Kaur Gill Sakdev Singh; Adlina Abdul Samad; Fakulti Pendidikan (2008)
Project Paper (Sarjana Muda Sains Pendidikan (Teaching English as Second Language)) - Universiti Teknologi Malaysia, 2008